1988
DOI: 10.1136/bmj.297.6653.910
|View full text |Cite
|
Sign up to set email alerts
|

Use of hospital beds: a cohort study of admissions to a provincial teaching hospital.

Abstract: An instrument was developed to study the use of hospital beds and discharge arrangements of a cohort of 847 admissions to the John Radcliffe Hospital, Oxford, for a three week period during February-March 1986. For only 38% of bed days were patients considered to have medical, nursing, or life support reasons for requiring a provincial teaching hospital bed. The requirements for a bed in the hospital decreased with the patient's age and length of stay in hospital. For only a tenth of patients was the general p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 10 publications
0
20
0
2
Order By: Relevance
“…Anderson et al developed a non-validated measure to examine the use of hospital beds and discharge arrangements 8. However, in their study a general practitioner was involved in only one in 10 patients due for discharge and only a third of patients were given more than 24 hours' notice of discharge.…”
Section: Validity and Reproducibilitymentioning
confidence: 99%
“…Anderson et al developed a non-validated measure to examine the use of hospital beds and discharge arrangements 8. However, in their study a general practitioner was involved in only one in 10 patients due for discharge and only a third of patients were given more than 24 hours' notice of discharge.…”
Section: Validity and Reproducibilitymentioning
confidence: 99%
“…4 A number of studies have reported on factors that in uence the duration of hospital stay and delay of discharge from hospital. [5][6][7][8] Less is known, however, about the characteristics of patients who make up the discharge delay list or the incidence and prevalence of such patients. The purpose of this study was to de ne the extent and duration of delayed discharge from acute medical (including surgical) hospital beds in Oxford.…”
Section: Introductionmentioning
confidence: 99%
“…5 In Oxford, the study found that 38% of days were appropriate, but this varied by ward and by age of the patients, with 50% of days being deemed appropriate for patients of 16-64 years, but only 19% for patients over 84; 'appropriateness' declined from 74% on the first day after admission to only 22% on the eighth day, and was related to the patterns of consultants' ward rounds; a suggestion was to delegate the discharge decision to other staff, and to involve GPs more in discharge planning. 4 …”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of this exercise include 1) the proportion of hospital beds occupied; 2) the proportion of beds that are inappropriately occupied; 3) the reasons for inappropriate bed occupation. In the literature there are several reports of such censuses carried out in the US," the UK 4 and South Africa. 3 However, to our knowledge no such exercise has been reported from a developing country setting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation